Engineering Methods and Software Support for Modeling and Design of Discrete-time Control of Distributed Parameter Systems - Hulkó, G.; Belavý, C.; Mészáros, A.; Bucek, P.; Ondrejkovic, K.; Zajícek, P. (European journal of control, 2009)
In this mini-tutorial some advanced engineering methods are presented for modeling and design of discretetime control of distributed parameter systems described for control purposes by numerical structures over complex-shape 3D definition domains along with the software package Distributed Parameter Systems Blockset for MATLAB & Simulink – Third-Party MathWorks product, inspired by the boom of numerical analysis of dynamics of machines and processes within engineering practice. The techniques offered are completed by a user-friendly web service tool, suitable for interactive solution of model control problems of distributed parameter systems via the Internet.